Influence of Products, Premium Pricing, and Service processes On Customer Satisfaction of Pt Asuransi Jiwa Taspen 2014-2018 Period - Kurnianto, Kharis; Nugroho, Setyo Aji; Priyambodo, Jati Tri (International Review of Management and Marketing, 2018)
This study discusses the extent of the influence of 3 variables, namely: Products, Determination of Premium Prices and Service Processes on Customer Satisfaction PT Taspen Life Insurance Period 2014 - 2018. Of these 3 variables the researcher made a research framework, namely: a) To what extent Products affect Customer Satisfaction, b) Determination of Premium Prices affect Customer Satisfaction, c) Service Process affects Customer Satisfaction, and d) The extent to which Products, Determination of Premium Prices and Service Processes together influence Customer Satisfaction. Questionnaire method is the choice of researchers in collecting data that will be processed using quantitative methods, multiple linear regression, while testing the hypothesis used hypothesis test t, test the hypothesis f with a significant level of 5%. Classical assumption tests used in this study include linearity test, normality test, homogeneity test, autocorrelation test, multicollinearity test and reliability test. Keywords: Insurance, Products, Prices, Premiums, Service Processes, Customer Satisfaction JEL Classifications: M31, I13, G22 DOI: https://doi.org/10.32479/irmm.7136